2011
DOI: 10.1021/bi2009344
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Mechanism of Hydroxylation by 4-Hydroxyphenylpyruvate Dioxygenase and Hydroxymandelate Synthase from Intermediate Partitioning in Active Site Variants

Abstract: 4-Hydroxyphenylpyruvate dioxygenase (HPPD) and hydroxymandelate synthase (HMS) each catalyze similar complex dioxygenation reactions using the substrates 4-hydroxyphenylpyruvate (HPP) and dioxygen. The reactions differ in that HPPD hydroxylates at the ring C1 and HMS at the benzylic position. The HPPD reaction is more complex in that hydroxylation at C1 instigates a 1,2-shift of an aceto substituent. Despite that multiple intermediates have been observed to accumulate in single turnover reactions of both enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 55 publications
4
53
0
Order By: Relevance
“…mitilis HPPD. 17,27 With ring-deuterated HPP inverse secondary KIE of 0.84 was obtained, which was interpreted as evidence for a change of hybridization from sp 2 to sp 3 on the carbon atom(s) directly bound to deuterium, i.e. direct attack of the ferryl species on the C1-C2 bond of the aromatic ring and formation of a 1,2-epoxide.…”
Section: Hmsmentioning
confidence: 99%
See 4 more Smart Citations
“…mitilis HPPD. 17,27 With ring-deuterated HPP inverse secondary KIE of 0.84 was obtained, which was interpreted as evidence for a change of hybridization from sp 2 to sp 3 on the carbon atom(s) directly bound to deuterium, i.e. direct attack of the ferryl species on the C1-C2 bond of the aromatic ring and formation of a 1,2-epoxide.…”
Section: Hmsmentioning
confidence: 99%
“…7 Similarities in sequences, structures and the reaction mechanisms of HMS and HPPD make these enzymes very attractive targets for mutagenesis experiments aimed at switching the hydroxylation specificity. [15][16][17] Results of mutagenesis studies showed that HMS is very tolerant to mutations and single, double and triple amino acid substitutions at conserved positions have not led to production of HG. 15,16 In the case of HPPD, analogous attempts were more successful and some mutants produced HMA.…”
Section: Hmsmentioning
confidence: 99%
See 3 more Smart Citations